2009
DOI: 10.1007/bf03326097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chromium on seed germination, root elongation and coleoptile growth in six pulses

Abstract: ABSTRACT:The ecotoxicological effects of Cr 2+ on germination and early seedling growth of six pulses were investigated. Seeds of these plants were exposed to seven different concentrations of Cr (0-3.2 mM). The results indicated that root elongation and coleoptile growth of six pulse plants were more sensitive than seed germination for measurement of the toxic of Cr 2+ pollutions. Different species show different levels of tolerance to Cr 2+ pollution. Lablab purpureus and Glycine max are the most sensitive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 24 publications
5
12
0
Order By: Relevance
“…Plants suitable for phytoremediation may be identified through investigation of germination parameters, plant growth and production under heavy metals contaminated media. It was reported that increasing amounts of certain heavy metals causes a decrease of germination and plant growth parameters in many plants ( Jun et al, 2009;Marques et al, 2007;Sengar et al, 2008). Loss of plant biomass by increasing levels of Cd toxicity occurred because processes of chlorophyll synthesis and photosynthesis were inhibited (Padmaja, 1990).…”
Section: Fresh and Dry Weightmentioning
confidence: 99%
“…Plants suitable for phytoremediation may be identified through investigation of germination parameters, plant growth and production under heavy metals contaminated media. It was reported that increasing amounts of certain heavy metals causes a decrease of germination and plant growth parameters in many plants ( Jun et al, 2009;Marques et al, 2007;Sengar et al, 2008). Loss of plant biomass by increasing levels of Cd toxicity occurred because processes of chlorophyll synthesis and photosynthesis were inhibited (Padmaja, 1990).…”
Section: Fresh and Dry Weightmentioning
confidence: 99%
“…It has been established that Cr compounds are highly toxic to plants and are detrimental to their growth and development, but some plants have demonstrated the ability to uptake, translocate, and tolerate even higher concentrations of Cr [10][11]. Other findings from Cr distribution in plants indicate that only a small proportion of Cr can be absorbed and translocated to aerial parts [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Seedling stage has been considered relatively sensitive to various toxic metals and allows rapid, early, cheap selection and would also show significant genetic variation and moderate to high heritability. Therefore, seedling traits have been extensively used for studying the responses of various populations to the metal stress and to select genotypes with differential tolerance (Rout, Samantaray, and Das 2000;Farooqi et al 2009;Jun, Ling, and Guanghua 2009;Yan and Tam 2013). We identified in our study that seedling traits such as shoot length sensitivity and shoot biomass provide an effective mean of selection for tolerant or susceptible genotype.…”
Section: Discussionmentioning
confidence: 83%